A stochastic game net‐based model for effective decision‐making in smart environments. (27th April 2016) - Sandhu, Rajinder; Sood, Sandeep K.
Summary: Internet of Things (IoT) in today's smart environments has many applications in gerontology, health care, transportation, and smart cities. Many challenges still exist in developing IoT‐based smart environments. Dynamic generation of action strategies based on multiple IoT object's input is one of the major challenges. In this paper, stochastic Petri nets and game theory are combined to create stochastic game nets (SGNs) for IoT‐based smart environment where each IoT device acts as a player with predefined place and action sets. Complete SGN will be created dynamically using individual sensor SGNs which will make IoT‐based smart environments highly interoperable and scalable. Proposed model is used to predict activities performed by two‐single person in their respective home with more than 70 sensors. Simulation results show suitability of proposed model in smart environments. Proposed model is tested for smart homes, but it can be used in any IoT‐based smart environment. Copyright © 2016 John Wiley & Sons, Ltd.